Interspecific Differentiation in Heavy Metals Concentration in Fishes of the Apa River, Upper Paraguay River Basin - Súarez, Yzel Rondon (2018)
Heavy metals concentration in fishes are important indicator geomorphological or environmental integrity in aquatic habitats. Aiming to evaluate metal concentration in fish muscles in Apa River, upper Paraguay basin, we analyzed 124 individuals of eight fish species at Cachoeira do Apa district (Porto Murtinho) from 2013 to 2014 belonging to Brycon hilarii, Leporinus friderici, Megaleporinus macrocephalus, Megaleporinus obtusidens, Piaractus mesopotamicus, Prochilodus lineatus, Pterodoras granulosus and Salminus brasiliensis. The samples were frozen and in the laboratory the musculature was removed, the samples were digested using the triacid method, and later the concentration of heavy metals was quantified in a flame atomic absorption spectrophotometer. There is a significant difference in the concentration of metals in fish (F=27.79, p<0.001). Considering the multivariate comparison of studied species, we observed that P. lineatus have a more different pattern of metal concentration, with P. granulosus also presenting a different pattern of others species. None species presented the concentration of metals above the limit defined by Brazilian legislation, however, species differed in their metal concentrations according to the position in the water column and feeding, suggesting that the integrated assessment of the concentration of metals may be an indicator of ecological differences in the obtaining of resources by species in aquatic communities. DOI: http://dx.doi.org/10.17807/orbital.v10i1.1040